2003
DOI: 10.2143/ac.58.4.2005289
|View full text |Cite
|
Sign up to set email alerts
|

Can serum lipid and CRP levels predict the 'severity' of aortic valve stenosis?

Abstract: We have demonstrated that severity of AVS does not correlate significantly with hypercholesterolaemia and CRP and their levels do not rise in accordance with increasing severity of AVS. Elevations of lipid levels in AVS were found to correlate with the presence of CAD rather than the severity of AVS. So, not in patients with simply AVS but in patients under higher cardiovascular risks, investigation of CRP plus lipid levels might provide benefit with respect to preventive treatment and benefit from cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…In those who underwent aortic valve replacement for aortic stenosis, CRP levels decreased from before to 6 months after valve replacement. C-reactive protein has also been studied in a nonsurgical population of aortic stenosis; in 60 patients with varying degrees of aortic stenosis, CRP levels did not correlate with stenosis severity (25). Recently, CRP has been localized in valve tissue of both calcific aortic-valve stenosis and degenerative aortic-valve bioprostheses (19), with a positive correlation between serum CRP levels and valvular CRP expression.…”
Section: Discussionmentioning
confidence: 99%
“…In those who underwent aortic valve replacement for aortic stenosis, CRP levels decreased from before to 6 months after valve replacement. C-reactive protein has also been studied in a nonsurgical population of aortic stenosis; in 60 patients with varying degrees of aortic stenosis, CRP levels did not correlate with stenosis severity (25). Recently, CRP has been localized in valve tissue of both calcific aortic-valve stenosis and degenerative aortic-valve bioprostheses (19), with a positive correlation between serum CRP levels and valvular CRP expression.…”
Section: Discussionmentioning
confidence: 99%
“…(1,15,16). High LDL, low high-density lipoprotein, high lipoprotein(a), cigarette smoking, obesity, diabetes mellitus, hypertension, and high C-reactive protein have all been shown to be statistically associated with AS (3,5,6,(17)(18)(19)(20)(21)(22). Hypercholesterolemia has been recurrently associated with AS in epidemiologic and histologic studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well accepted that atherosclerosis has an inflammatory component and that its related markers predict acute coronary events. Several studies also showed that inflammation is involved in the pathogenesis of nonrheumatic AS (37,(43)(44)(45). The expanded abdominal adipose depot in patients with MS could represent an important source of cytokine (e.g., interleukin-6, tumor necrosis factor-alpha) production (46)(47)(48)(49).…”
Section: It Is Well Known That Hdl Cholesterol Has Antioxidantmentioning
confidence: 99%